Key Odorants Regulate Food Attraction in Drosophila melanogaster - Giang, Thomas; He, Jianzheng; Belaidi, Safaa; Scholz, Henrike (Frontiers in Behavioral Neuroscience, 2017)
In insects, the search for food is highly dependent on olfactory sensory input. Here, we investigated whether a single key odorant within an odor blend or the complexity of the odor blend influences the attraction of Drosophila melanogaster to a food source. A key odorant is defined as an odorant that elicits a difference in the behavioral response when two similar complex odor blends are offered. To validate that the observed behavioral responses were elicited by olfactory stimuli, we used olfactory co-receptor Orco mutants. We show that within a food odor blend, ethanol functions as a key odorant. In addition to ethanol other odorants might serve as key odorants at specific concentrations. However, not all odorants are key odorants. The intensity of the odor background influences the attractiveness of the key odorants. Increased complexity is only more attractive in a concentration-dependent range for single compounds in a blend. Orco is necessary to discriminate between two similarly attractive odorants when offered as single odorants and in food odor blends, supporting the importance of single odorant recognition in odor blends. These data strongly indicate that flies use more than one strategy to navigate to a food odor source, depending on the availability of key odorants in the odor blend and the alternative odor offered.